An Introduction strictu sensu. Malinowski aboard carrier ARA 25 de Mayo - Guber, Rosana (2022)
This paper shows how we can use the Introduction of Bronislav Malinowski’s The Argonauts of the Western Pacific in our research today, a century later. In this specific case, and going through a double commemoration in 2022, I explain the logic with which I structured an ethnographic method class in April 2021. I did so by taking advantage of a subject that was foreign enough to my students, prompting them to raise questions and to understand the structure, the imponderabilia of real life and the natives’ mentality. In my own case, the natives are the real Other of the Argentine academia: the military sailors of the Argentine Navy, with whom I tried to understand how they experienced the Anglo-Argentine conflict for the Malvinas/Falklands and other South Atlantic Islands (1982).